Assessing the role of fertility levels and biofertilizers on growing degree days, NDVI and chlorophyll in malt barley (Hordeum vulgare) - SONAL ATHNERE; P C CHAPLOT; RAJENDRA PATEL; SURYAKANT NAGRE; KANGUJAM BOKADO; PINKY YADAV; SUNDAR ANCHRA (The Indian Journal of Agricultural Sciences)
The experiment was conducted during 2020–2022 at Maharana Pratap University of Agriculture and Technology, Udaipur, Rajasthan to assess the impact of different fertility levels and biofertilizer treatments on malt barley (Hordeum vulgare L.). The experiment followed a factorial randomized block design (Factorial-RBD) and included 15 treatment combinations comprised of three fertility levels, viz. application of 70 kg N+40 kg P2O5 +25 kg K2O/ha (N70P40K25), 60 kg N+30 kg P2O5 +20 kg K2O/ha (N60P30K20) and 50 kg N+25 kg P2O5 +15 kg K2O/ha (N50P25K15) with five liquid biofertilizers i.e. control, Azotobacter, PSB, KMB and Azotobacter + PSB + KMB. The malt barley cultivar 'DWRB-137' served as the experimental crop. The findings indicated that the malt barley, when supplemented with (N70P40K25) kg/ha recorded the highest growing degree at heading stage, 50% anthesis, 7, 14, 21 days after 50% anthesis and physiological maturity (1601.57ºC day), normalized difference vegetation index at 50% anthesis, 7, 14 and 21 days after 50% anthesis (0.734) and chlorophyll content in leaves represented significant increase as compared to other fertility levels. Furthermore seed inoculated with Azotobacter + PSB + KMB significantly increased growing degree at heading stage, 50% anthesis, 7, 14 and 21 days after 50% anthesis (1264.49ºC day) and chlorophyll content in leaves.